Audio-visual priming in 7-month-old infants: an ERP study - Peykarjou, Stefanie; Wissner, Julia; Pauen, Sabina (Infant behavior and development, 2020)
The current study investigates categorical priming across modalities in 7-month-old infants using electroencephalographic (EEG) measures. In two experiments, infants were presented with sounds as primes, followed by images of human figures and furniture items as targets. In experiment 1 (N = 20), images were preceded by infant-directed (ID) or adult-directed (AD) speech to explore effects of intermodal categorical mismatches. Furniture targets (mismatching category) elicited an increased amplitude of the Negative central (Nc) component compared to human targets (matching category), p < .01, indicating increased attention. Results did not vary with manner of speaking (ID or AD). Experiment 2 (N = 17) explored whether a categorical mismatch between prime and target would elicit increased positive slow wave (PSW) amplitudes for human targets, indicating increased memory effort. Here, bicycle ringtones and ID speech served as primes. Again, furniture targets elicited an increased Nc regardless of prime category, p < .05, and a categorical change from human speech to furniture target images elicited an increased PSW, p < .05. No PSW effect was found for human targets following bicycle ringtones, however. The experiments reported here suggest that auditory primes may increase infant attention and memory updating particularly for non-social, categorically mismatching stimuli.